A Social History of Spanish Labour. New Perspectives on Class, Politics and Gender - Shubert, Adrian (Labour / Le Travail, 2009)
The article reviews the book, "A Social History of Spanish Labour: New Perspectives on Class, Politics and Gender," edited by José A. Piqueras and Vicent Sanz Rozalén.
Keywords: BOOKS -- Reviews; History; Labor; Nonfiction; PIQUERAS, Jose A.; ROZALEN, Vicent Sanz; SOCIAL History of Spanish Labour: New Perspectives on Class, Politics & Gender, A (Book); SPAIN; Social history